Exploring Effective Reading Tasks for Senior High School: Addressing Key Gaps Using Barrett’s Taxonomy - Junaidi, Elwa; Zainil, Yetti; Junaidi, Junaidi (Elsya : Journal of English Language Studies, 2024)
This study addresses a critical gap in high school reading instruction by analyzing the development needs of reading comprehension tasks through the lens of Barrett’s Taxonomy. Despite its established utility in structuring comprehension levels, Barrett’s Taxonomy is underutilized in Indonesian high school curricula, leaving a gap in tasks that adequately foster inferential and evaluative skills. Aiming to bridge this gap, this research employed a cluster random sampling method to select six high schools in Padang, effectively capturing a representative sample of English teachers’ perspectives. Data were gathered through questionnaires and structured interviews with one teacher from each school, focusing on their preferences for reading task content and structure. Results reveal that teachers highly prioritize reorganization, inferential comprehension, evaluation, and appreciation, with a slightly lower emphasis on literal comprehension. Furthermore, teachers favored content areas such as significant phenomena, culture, science and technology, health, social issues, and natural disasters across various text types. Identified areas for task improvement include enhancing topic diversity, aligning texts with students' cultural backgrounds and proficiency levels, and incorporating higher-order thinking skills (HOTS). The study’s findings underscore the need for culturally relevant, cognitively engaging tasks that support both language acquisition and critical thinking skills. In the broader context, this research contributes valuable insights for curriculum developers and educators worldwide, advocating for reading tasks that align with global educational priorities to foster analytical skills, thereby preparing students to navigate complex information landscapes.